THE RIGHT TO HUMAN DIGNITY AND WANDERINGS OF THE CONSTITUTIONAL COURT OF SERBIA - Simovic, Darko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
Human dignity is constitutionalized in Serbia as a constitutional value, as a separate human right, but also as a segment of certain human rights. Despite the fact that the sphere of constitutionalizing human dignity has been significantly expanded, the catalogue of human and minority rights begins with the right to human dignity. The role given to that right implies that it is of particular value. Nevertheless, the right to human dignity is still on the margins of theoretical framework. Currently, the Constitutional Court lacks a consistent approach to developing the doctrine of the right to human dignity. Besides the fact that the approach of the Constitutional Court changed radically, in the majority of those cases, the Constitutional Court only declaratively referred to the right to human dignity, without specifying the content of that right. The inconsistency in the approach of the Constitutional Court led to extreme uncertainty regarding the scope of that right, so that even after approximately two decades of the Constitution, it cannot be said what constitutes the minimum core of the right to human dignity.
Keywords: Human dignity, Constitution, Constitutional Court of Serbia, Human rights, Proportionality.